Frequency and outcomes of brain metastases in patients with HER2‐mutant lung cancers. Issue 24 (30th August 2019) - Offin, Michael; Feldman, Daniel; Ni, Ai; Myers, Mackenzie L.; Lai, W. Victoria; Pentsova, Elena; Boire, Adrienne; Daras, Mariza; Jordan, Emmet J.; Solit, David B.; Arcila, Maria E.; Jones, David R.; et al.
Abstract : Background: Mutations in human epidermal growth factor receptor 2 ( HER2 ; also known as ERBB2 ) are found in approximately 2% of lung adenocarcinomas. The frequency and clinical course of brain metastases in this oncogenic subset are ill defined. Methods: Baseline and subsequent development of brain metastases was evaluated in consecutive patients with HER2 ‐mutant (n = 98), epidermal growth factor receptor ( EGFR )–mutant (n = 200), and KRAS ‐mutant lung cancers (n = 200). Results: At metastatic diagnosis, the odds ratio (ORs) for brain metastases was similar for patients whose tumors harbored HER2 mutations (19%) in comparison with patients with KRAS mutations (24%; OR for HER2 vs KRAS, 0.7; P = .33) but lower compared to patients with EGFR mutations (31%; OR for HER2 vs EGFR, 0.5; P = .03). Patients with lung cancer and HER2 mutations developed more brain metastases on treatment than patients with KRAS mutations (28% vs 8%; hazard ratio [HR], 5.2; P < .001) and trended more than patients with EGFR mutations (28% vs 16%; HR, 1.7; P = .06). Patients with HER2 YVMA mutations also developed more brain metastases on treatment than patients with KRAS mutations (HR, 5.9; P < .001). The median overall survival (OS) was shorter for patients with HER2 ‐mutant (1.6 years; P < .001) or KRAS ‐mutant lung cancers (1.1 years; P < .001) than patients with EGFR ‐mutant lung cancers (3.0 years). Brain metastases occurred in 47% of patients with HER2 ‐mutant lung cancers, which imparted shorter OS (HR, 2.7; P < .001). Conclusions: These data provide a framework for brain imaging surveillance in patients with HER2 ‐mutant lung cancers and underpin the need to develop HER2‐targeted agents with central nervous system activity. Abstract : Oncogenic driver mutations influence the disease course, treatment options, and development of brain metastases in patients with lung cancers. Results from this retrospective analysis of 498 patients with HER2 ‐, KRAS ‐, or EGFR ‐mutant lung cancers show that patients with HER2 ‐driven lung cancers have reduced overall survival and are at increased risk for developing brain metastases while they are on treatment.